2019
DOI: 10.1186/s12888-019-2378-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions for managing postpartum psychosis: a qualitative analysis of women’s and family members’ experiences and preferences

Abstract: BackgroundPostpartum psychosis is a rare, yet severe disorder, in which early identification and immediate intervention are crucial. Despite recommendations for psychological input, little is known about the types of psychological intervention reported to be helpful. The aim of this study was to explore the experiences, needs and preferences for psychological intervention from the perspective of women with postpartum psychosis and from the perspective of family members.MethodsThirteen women and eight family me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 48 publications
0
45
0
2
Order By: Relevance
“…Debbie provided an illustration of this when she felt unsupported by her midwife and Nancy who felt unsupported by her husband. Previous qualitative research highlighted this need for women who shared how much they valued and needed family and friends' support in their recovery from postpartum psychosis (Forde et al, 2019;Heron et al, 2012). McGrath et al (2013) also reported that important to women's recovery was the context of factors in their lives such as informal support networks, women with similar experiences, and the mental health system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Debbie provided an illustration of this when she felt unsupported by her midwife and Nancy who felt unsupported by her husband. Previous qualitative research highlighted this need for women who shared how much they valued and needed family and friends' support in their recovery from postpartum psychosis (Forde et al, 2019;Heron et al, 2012). McGrath et al (2013) also reported that important to women's recovery was the context of factors in their lives such as informal support networks, women with similar experiences, and the mental health system.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen women who had postpartum psychosis and eight family members from the United Kingdom were interviewed about their experiences of postpartum psychosis, interventions and support, and the family's role (Forde et al, 2019). Interview data were analyzed using thematic analysis.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…As a result, those patients are completely unprepared for what they are facing. Many times, the lack of information and prior counseling creates a feeling of shame, which may prevent her relatives from seeking help [13]. In the acute phase of PP, patients experience loss of their identity and sense of self, feel abandoned by their family and fear for the future [14].…”
Section: The Social Effects Of Postpartum Psychosis In a Woman's Lifementioning
confidence: 99%
“…Even after the psychotic symptoms have passed the feeling of losing control and upset in every aspect of their life remains. Therefore, the need for support from the family, both during their hospitalization and afterwards, is considered imperative [13]. The couple's decision to have another child in the future is also affected [12].…”
Section: The Social Effects Of Postpartum Psychosis In a Woman's Lifementioning
confidence: 99%
See 1 more Smart Citation